Ethylene dimethacrylate used as an NH3 adsorbent with high adsorption capacity and selectivity. (April 2022) - Han, Zhangliang; Tian, Haozhong; Pang, Xiaobing; Song, Guoyong; Sun, Dezhi
Abstract: NH3 molecularly imprinted polymers (NH3 -MIPs) were synthesized that could successfully separate and recover NH3 during sludge aerobic composting; however, increased toluene usage during the adsorbent preparation incurred a high cost and severe environmental risks. The purpose of this study was to reduce toluene usage by optimizing the reagent composition of NH3 -MIPs, based on maintaining a high NH3 adsorption capacity and selectivity. Five adsorbent groups, including NH3 -MIPs, and NH3 -Ethylene dimethacrylate adsorbents (NH3 -EGDMA) with 0%, 75%, 90%, and 100% toluene reduction efficiencies, were prepared and tested for their adsorption performance. The results showed that NH3 -EGDMA with 75% toluene reduction not only had a high NH3 adsorption capacity (104.42 mg g −1 ) but also had a high separation factor for NH3 /methyl sulfide (3121) and NH3 /dimethyl disulfide (4597). The adsorption mechanism was identified as a chemical force between NH3 and NH3 -EGDMA with a 75% toluene reduction using the analysis of the kinetic model. This study significantly reduces NH3 adsorbent cost as well as harm to the environment during the adsorbent preparation, which was beneficial to the popularization and application of this NH3 adsorbent. Graphical abstract: Image 1 Highlights: NH3 -EGDMA adsorbent was successfully synthesized via a precipitation polymerization. NH3 -EGDMA had a high NH3 adsorption capacity with high NH3 selectivity. Reduction of 75% toluene and 44% cost for the NH3 adsorbent was reached. The adsorption mechanism was identified using the analysis of the kinetic model.